PENGARUH TIME PRESSURE DAN RISIKO AUDIT TERHADAP PREMATURE SIGN OFF PROSEDURE AUDIT PADA KAP (KANTOR AKUNTUN PUBLIK) SULAWESI SELATAN DI MAKASSAR - Syamsuri Rahim; Nur Wahyuni; Zulkifli Habie (AkMen JURNAL ILMIAH, 2023)
This study aims to test the influence of Time Pressure (Time Pressure) and Audit Risk Against Premature Sign Off Prosedure Audit At KAP (Public Accounting Firm) South Sulawesi In Makassar. The results of this study show that: 1) Time pressure has a positive and significant effect on Premature sign off audit procedures, shown with t count value of 4,071 with significance of 0.000. The value of significance is below 0.05. 2) Audit risk has a positive and significant effect on Premature sign off audit procedure, shown by t value obtained by 4,332 with significance equal to 0.000. The value of significance is below 0.05. The influence of Time Pressure and Audit Risk together give 59,6% influence to Premature sign off procedure audit While the rest equal to 40,4% determined by other factor.